France. - Williams, Nicola, ....- (Footscray : Lonely Planet, 2011)
Welcome to France, a country that seduces travellers with its unfalteringly familiar culture woven around café terraces, village-square markets and lace-curtained bistros with their plat du jour (dish of the day) chalked on the board... France is all about world-class art and architecture, Roman temples and Renaissance châteaux, iconic landmarks known the world over, and of course, there's that fine food and wine that woos so many travellers.
Keywords: Frankrijk -- Reisgidsen